Supercritical foaming PHA / PBAT composite material and preparation method and application thereof
By introducing PBAT, chain extender and self-assembly nucleating agent into PHA/PBAT composite materials, and using supercritical foaming technology and steam forming process, the phase separation, poor toughness and bubble collapse problems of composite materials during foaming are solved, and efficient foaming and stability improvement are achieved, which is suitable for the application of packaging materials.
Patent Information
- Application Number
- CN202411724502.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing PHA/PBAT composite materials have phase separation phenomena, poor toughness, slow crystallization rate, low cell density and bubble collapse phenomena during foaming, which limits their use in packaging material applications.
By introducing PBAT, chain extender and self-assembled nucleating agent, the melt strength and toughness of PHA are improved, and efficient foaming PHA/PBAT composites are prepared through supercritical foaming technology and steam molding process.
It significantly improves the foaming efficiency and overall stability of PHA/PBAT composite materials, improves the cell density and crystallization rate, solves the bubble collapse phenomenon, and the wall thickness of the foamed plastic cup is less than 2mm, which is suitable for packaging material applications.
Smart Images

Figure BDA0005158861370000041 
Figure HDA0005158861380000011 
Figure HDA0005158861380000012
Abstract
Description
Technical Field
[0001] The present invention relates to a foaming composite material and a preparation method and application thereof, and in particular to a supercritical foaming PHA / PBAT composite material and a preparation method and application thereof. Background Art
[0002] At present, a large number of non-degradable plastic foams are widely used in the fields of construction, food packaging and agricultural packaging due to their advantages such as light weight and good thermal insulation. This non-degradable plastic foam has caused serious environmental pollution, especially in the marine environment, where it cannot be degraded to form a large amount of plastic pollution. Although conventional biomaterials such as PLA have degradable properties, they cannot be truly degraded in the marine environment. In order to solve the problem of marine plastic foam pollution, the development of biodegradable foaming materials as a green solution is gaining increasing attention. Polyhydroxyalkanoates (PHAs) are a class of biodegradable polyesters synthesized by bacteria through a fermentation process. They have attracted widespread attention for their biodegradability, biocompatibility, marine degradability and renewable resource utilization. However, PHA also has disadvantages such as slow crystallization rate, poor toughness and low foamability, which limit its application in some fields.
[0003] Polybutylene adipate-terephthalate (PBAT) is a biodegradable thermoplastic polyester that combines the properties of aliphatic and aromatic polyesters, with good flexibility, processing properties and biodegradability. However, PBAT has a high cost, low crystallinity and limited physical properties.
[0004] Supercritical foaming technology is a safe, green and environmentally friendly technology. Patent CN114891261B discloses a method for preparing plant fiber PHA foaming material, which uses chemical grafting modification to improve the foamability of PHA, but there are problems such as chemical reagent residues and low foaming ratio. Patent CN102229707A provides a method for preparing PBAT molded foaming material, but the PBAT foaming particles used alone are relatively soft and not suitable for packaging material applications.
[0005] At present, there are several problems in the preparation of PHA / PBAT composite materials: (1) There is a phase separation phenomenon between PHA and PBAT, which easily leads to pore rupture when small particles are foamed; (2) PHA has poor toughness and slow crystallization rate, which hinders pore growth, low pore density, and large pore size; (3) PHA has low melt strength and poor pore support, which leads to easy bubble collapse during steam thin-wall molding; (4) Products molded by conventional foaming molding technology generally have large wall thickness and cannot be directly applied. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a supercritical foaming PHA / PBAT composite material that can improve the melt strength of PHA, improve the toughness of PHA, and enhance the foaming efficiency and overall stability of the composite material;
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned supercritical foaming PHA / PBAT composite material;
[0008] The third object of the present invention is to provide applications of the above-mentioned supercritical foamed PHA / PBAT composite material.
[0009] Technical solution: The supercritical foamed PHA / PBAT composite material of the present invention comprises the following components in parts by weight:
[0010] PHA: 60-90 parts;
[0011] PBAT: 10-40 parts;
[0012] Chain extender: 0.5-2.0 parts;
[0013] Self-assembly nucleating agent: 0.2-0.8 parts;
[0014] Anti-hydrolysis agent: 0.1-0.5 parts.
[0015] Wherein, the PHA is at least one of PHB, PHBV, PHBHHx, and P(3HB, 4HB). Preferably, the PHA includes but is not limited to the product with the brand name XF-1000 produced by Hangzhou Xinfu Biotechnology Co., Ltd., the product with the brand name Y-1000P produced by Zhejiang Tianan Biotechnology Co., Ltd., and the product with the brand names BP330 and BP350 produced by Blue Crystal Microorganism Co., Ltd.; preferably, the PHA is the product with the brand name BP330 produced by Blue Crystal Microorganism Co., Ltd.
[0016] Wherein, the melt index of the PBAT is ≤7g / 10min, and the tensile strength is ≥18Mpa. Preferably, the PBAT includes but is not limited to the product with the brand name JH-1908 produced by Jinhui Zhaolong High-tech Technology Co., Ltd., the product with the brand name PBAT-7000 produced by Shanghai Tongcheng New Materials Group Co., Ltd., the product with the brand name C1200 of BASF of Germany, and the product with the brand name TH801T produced by Blue Mountain Tunhe Technology Co., Ltd.; preferably, the PBAT is the product with the brand name JH-1908 produced by Jinhui Zhaolong High-tech Technology Co., Ltd.
[0017] Wherein, the chain extender is at least one of the epoxy chain extenders ADR series, oxazoline, and isocyanate. Preferably, the chain extender includes but is not limited to at least one of ADR-4300, ADR-4370, or ADR-4400; the chain extender is preferably an epoxy chain extender, and more preferably, the chain extender is ADR-4400.
[0018] Wherein, the self-assembly nucleating agent is a hydrazide and / or an amide; the self-assembly nucleating agent is at least one of sebacic acid dibenzohydrazide, adipic acid diphenyl dihydrazide, and an amide nucleating agent; preferably, the amide nucleating agent is at least one of octenylamide, stearic acid amide, and lauryl amide; the model of the sebacic acid dibenzohydrazide is TMC-300, and the model of the adipic acid diphenyl dihydrazide is TMC-306; more preferably, the self-assembly nucleating agent is a hydrazide TMC-328, which is a bio-based supporting nucleating agent.
[0019] Wherein, the anti-hydrolysis agent is at least one of carbodiimide, isocyanate, and acid anhydride; preferably, the anti-hydrolysis agent is carbodiimide.
[0020] The preparation method of the supercritical foamed PHA / PBAT composite material comprises the following steps:
[0021] (1) mixing PHA and PBAT, adding a chain extender, a self-assembly nucleating agent and an anti-hydrolysis agent, and stirring to obtain mixed particles;
[0022] (2) melt-mixing and extruding the mixed particles through a twin-screw extruder, pelletizing the particles underwater to obtain modified particles, and drying the particles;
[0023] (3) The dried modified particles are subjected to supercritical foaming to obtain supercritical foamed beads.
[0024] Wherein, in step (1), PHA and PBAT are dried at 70-80° C. for 2-4 hours respectively to ensure that moisture is removed; the dried PHA and PBAT are added to a high-speed mixer in proportion and mixed for 3-5 minutes; a chain extender, a self-assembly nucleating agent, and an anti-hydrolysis agent are added in sequence, and stirring is continued for 5-8 minutes to ensure uniform dispersion; wherein the operating speed of the high-speed mixer is 500-2000 rpm; preferably, the speed of the high-speed mixer is 1500 rpm.
[0025] Wherein, in step (2), when a twin-screw extruder is used, the extrusion temperature is controlled at 140-180°C, the screw speed is 50-80rpm, and the modified particles are obtained by underwater pelletizing, and the pelletizer speed is 2500-3500 rpm; preferably, the pelletizer speed is 3000 rpm.
[0026] Wherein, in step (3), the modified particles are placed in a supercritical high-pressure reactor, supercritical foaming gas is injected through a booster pump, and the pressure is quickly reduced to atmospheric pressure after foaming is completed to obtain supercritical foaming beads; the supercritical foaming gas is one or both of supercritical CO2 and supercritical N2; the foaming temperature is 100-120°C, the saturation pressure is 10-20MPa, and the pressure holding time is 10-30min.
[0027] The above-mentioned supercritical foamed PHA / PBAT composite material is used in the preparation of degradable thermal insulating thin-walled plastic cups.
[0028] Among them, the supercritical foaming PHA / PBAT composite material is pre-pressed and then steam-molded to obtain a degradable thermal insulation foam plastic cup.
[0029] The supercritical foamed particles are placed in a pre-pressurization tank with a holding pressure of 1-3kg and a holding time of 4-6h. After the holding pressure is completed, they are released for standby use. The pre-pressurized foamed beads are then bonded through a steam molding process to prepare a biodegradable heat-insulating foamed plastic cup with a wall thickness of less than 2mm.
[0030] The steam molding process conditions are: solid mold pressure 0.3-1kg, transfer mold pressure 0.3-1kg, solid mold heating 10-30s, transfer mold heating 10-30s, double-sided pressure 0.5-1.5kg, double-sided heating 20-50s, water cooling 50-150s, and mold gap 10-25s.
[0031] Principle of the invention: PHA is completely biodegradable, but its slow crystallization rate and poor toughness lead to problems such as low foamability of modified particles and poor foam performance of beads. PHA is improved by introducing PBAT to make it more suitable for the molding of complex structures. Its molecular structure is chain extended and branched to improve the melt strength of PHA and improve the poor toughness of PHA. In combination with the use of a self-assembling nucleating agent, the self-assembling nucleating agent forms a fibril network structure during the twin-screw melt extrusion process. This self-assembled fiber induces the PHA / PBAT blend to accelerate the crystallization rate, improve the pore uniformity and density of the PHA material, and improve the foaming efficiency and overall stability.
[0032] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:
[0033] (1) The epoxy group of the chain extender reacts with the terminal carboxyl groups of PHA and PBAT to form a unique molecular chain cross-linked grid structure of PHA-g-PBAT, which reduces the interfacial force between the two phases of PHA and PBAT, greatly improves the poor compatibility of PHA and PBAT, greatly improves the melt strength, and improves the inherent toughness problem of PHA; (2) The synergistic effect of the chain extender and the self-assembly nucleating agent enables the material to exhibit better performance in structural packaging applications, especially the application of the self-assembly nucleating agent, so that a fibril network structure is formed inside the composite material of the present invention. This structure is not only an improvement of heterogeneous nucleation sites, but also accelerates crystallization in a new way, significantly improving the cell density and foaming stability. (3) The collapse phenomenon of the foamed plastic cup during steam molding is improved, and at the same time, the wall thickness of the foamed plastic cup is less than 2mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The SEM images of the simple blend of PHA / PBAT in Comparative Example 1 and the improved one after adding the chain extender in Example 1;
[0035] Figure 2 These are SEM images of the bead foaming materials of Example 1 with the addition of a self-assembly nucleating agent and Comparative Example 3 without the addition of a self-assembly nucleating agent. DETAILED DESCRIPTION
[0036] The present invention is described in further detail below.
[0037] Example 1
[0038] (1) Dry the blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 at 75°C for 3 hours to ensure that the moisture is removed and set aside.
[0039] (2) After drying, 70% by weight of blue crystal microorganism PHA-BP330 and 30% by weight of Jinhui Zhaolong PBAT-1908 were added to a high-speed mixer and stirred for 5 minutes at a speed of 1500 rpm. Then, 0.5 parts by weight of chain extender: ADR-4400; 0.2 parts by weight of self-assembly nucleating agent: TMC-328; and 0.1 parts by weight of anti-hydrolysis agent: carbodiimide were weighed; and the mixture was added to the high-speed mixer in sequence and stirred for 7 minutes at a speed of 1500 rpm. The mixture was discharged for standby use.
[0040] (3) adding the mixed material of step (2) into a twin-screw extruder for melt extrusion, cooling, and underwater pelletizing to obtain modified particles; wherein the temperatures of the zones of the twin-screw extruder of the embodiments of the present invention and the comparative example are as follows: 140°C, 170°C, 170°C, 175°C, 175°C, 180°C, 180°C, 175°C, 175°C; the die head temperature is 180°C; the screw speed is 60 rpm; and the pelletizer speed is 3000 rpm.
[0041] (4) The modified particles obtained in step (3) are used to prepare foamed beads using a supercritical foaming device under the conditions of a foaming temperature of 100° C., a saturation pressure of 15 MPa, and a saturation time of 30 min, wherein the supercritical foaming gas is CO2 and N2 in a ratio of 3:1; the foaming ratio of the obtained PHA / PBAT composite foam material is 14.3 times, wherein the foaming ratio (VER) of the foam particles of the present invention is calculated using the following formula:
[0042]
[0043] where ρ f is the density of the unexpanded particles, ρ p is the density of the expanded foam, in g / cm 3 , and its VER was measured by an analytical balance (BSA3202S, Sartorius, Germany).
[0044] (5) The foamed particles obtained in step (4) are placed in a pre-pressurization tank for pressure maintenance, with a compressed air pressure of 1 kg and a pressure maintenance time of 4 hours, and then steam-formed by a steam molding device to obtain a biodegradable thermal insulation foamed thin-wall plastic cup.
[0045] Example 2
[0046] (1) Dry the blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 at 75°C for 3 hours and set aside.
[0047] (2) After drying, 70% by weight of blue crystal microorganism PHA-BP330 and 30% by weight of Jinhui Zhaolong PBAT-1908 were added to a high-speed mixer and stirred for 5 minutes, and then the chain extender: ADR-4400, the weight portion is 1.0 parts; the self-assembly nucleating agent: TMC-328, the weight portion is 0.2 parts; the anti-hydrolysis agent: carbodiimide, the weight portion is 0.1 parts; add them to the high-speed mixer in sequence and stir for 7 minutes, and discharge the material for standby use.
[0048] (3) adding the mixed material of step (2) into a twin-screw extruder for melt extrusion, cooling, and underwater pelletizing to obtain modified particles; the screw speed is 60 rpm; the pelletizer speed is 3000 rpm.
[0049] (4) The modified particles obtained in step (3) are used to prepare foamed beads using a supercritical foaming device under the conditions of a foaming temperature of 100° C., a saturation pressure of 15 MPa, and a saturation time of 30 min, wherein the supercritical foaming gas is CO2 and N2 in a ratio of 3:1; the obtained PHA / PBAT composite foam material has a magnification of 21.5 times.
[0050] (5) The foamed particles obtained in step (4) are placed in a pre-pressurization tank for pressure maintenance, with a compressed air pressure of 1 kg and a pressure maintenance time of 4 hours, and then steam-formed by a steam molding device to obtain a biodegradable thermal insulation foamed thin-wall plastic cup.
[0051] Example 3
[0052] (1) Dry the blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 at 75°C for 3 hours and set aside.
[0053] (2) After drying, 70% by weight of blue crystal microorganism PHA-BP330 and 30% by weight of Jinhui Zhaolong PBAT-1908 were added to a high-speed mixer and stirred for 5 minutes, and then the chain extender: ADR-4400, the weight portion is 1.5 parts; the self-assembly nucleating agent: TMC-328, the weight portion is 0.2 parts; the anti-hydrolysis agent: carbodiimide, the weight portion is 0.1 parts; add them to the high-speed mixer in sequence and stir for 7 minutes, and discharge the material for standby use.
[0054] (3) adding the mixed material of step (2) into a twin-screw extruder for melt extrusion, cooling, and underwater pelletizing to obtain modified particles; the screw speed is 60 rpm; the pelletizer speed is 3000 rpm.
[0055] (4) The modified particles obtained in step (3) are used to prepare foamed beads using a supercritical foaming device under the conditions of a foaming temperature of 100° C., a saturation pressure of 15 MPa, and a saturation time of 30 min, wherein the supercritical foaming gas is CO2 and N2 in a ratio of 3:1; the obtained PHA / PBAT composite foam material has a magnification of 31.5 times.
[0056] (5) The foamed particles obtained in step (4) are placed in a pre-pressurization tank for pressure maintenance, with a compressed air pressure of 1 kg and a pressure maintenance time of 4 hours, and then steam-formed by a steam molding device to obtain a biodegradable thermal insulation foamed thin-wall plastic cup.
[0057] Example 4
[0058] (1) Dry the blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 at 75°C for 3 hours and set aside.
[0059] (2) After drying, 70% by weight of Cyanobacteria PHA-BP330 and 30% by weight of Jinhui Zhaolong PBAT-1908 were added to a high-speed mixer and stirred for 5 minutes. Then, 2.0 parts by weight of chain extender: ADR-4400; 0.2 parts by weight of self-assembly nucleating agent: TMC-328; and 0.1 parts by weight of anti-hydrolysis agent: carbodiimide were weighed. The mixture was added to a high-speed mixer in sequence and stirred for 7 minutes. The mixture was discharged for standby use.
[0060] (3) adding the mixed material of step (2) into a twin-screw extruder for melt extrusion, cooling, and underwater pelletizing to obtain modified particles; the screw speed is 60 rpm; the pelletizer speed is 3000 rpm.
[0061] (4) The modified particles obtained in step (3) are used to prepare foamed beads using a supercritical foaming device under the conditions of a foaming temperature of 100° C., a saturation pressure of 15 MPa, and a saturation time of 30 min, wherein the supercritical foaming gas is CO2 and N2 in a ratio of 3:1; the obtained PHA / PBAT composite foam material has a magnification of 24.4 times.
[0062] (5) The foamed particles obtained in step (4) are placed in a pre-pressurization tank for pressure maintenance, with a compressed air pressure of 1 kg and a pressure maintenance time of 4 hours, and then steam-formed by a steam molding device to obtain a biodegradable thermal insulation foamed thin-wall plastic cup.
[0063] Example 5
[0064] The modified preparation process of the composite material of blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 in this embodiment is the same as that in Example 4, except that the foaming temperature is 105°C and the saturation pressure is 15MPa. The ratio of the obtained PHA / PBAT composite foam material is 26.6 times. The foamed particles are placed in a pre-pressurized tank for pressure maintenance, the compressed air pressure is 1kg, the pressure maintenance time is 4h, and then steam-molded by a steam molding device to obtain a degradable thermal insulation foamed thin-walled plastic cup.
[0065] Example 6
[0066] The modified preparation process of the composite material of Cyanobacteria PHA-BP330 and Jinhui Zhaolong PBAT-1908 in this embodiment is the same as that in Example 4, except that the foaming temperature is 110°C and the saturation pressure is 15MPa. The ratio of the obtained PHA / PBAT composite foam material is 28 times. The foamed particles are placed in a pre-pressurized tank for pressure maintenance, the compressed air pressure is 1kg, the pressure maintenance time is 4h, and then steam-molded by a steam molding device to obtain a degradable thermal insulation foamed thin-walled plastic cup.
[0067] Example 7
[0068] The modified preparation process of the composite material of blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 in this embodiment is the same as that in Example 4, except that the foaming temperature is 115°C and the saturation pressure is 15MPa. The ratio of the obtained PHA / PBAT composite foam material is 20.8 times. The foamed particles are placed in a pre-pressurized tank for pressure maintenance, the compressed air pressure is 1kg, the pressure maintenance time is 4h, and then steam-molded by a steam molding device to obtain a degradable thermal insulation foamed thin-walled plastic cup.
[0069] Comparative Example 1
[0070] (1) Dry the blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 at 75°C for 3 hours and set aside.
[0071] (2) After drying, 70% by weight of Cyanobacteria PHA-BP330 and 30% by weight of Jinhui Zhaolong PBAT-1908 were added to a high-speed mixer and stirred for 5 minutes. Then, 0.1 parts by weight of anti-hydrolysis agent: carbodiimide were weighed and added to the high-speed mixer in sequence and stirred for 7 minutes. The mixture was discharged for standby use.
[0072] (3) adding the mixed material of step (2) into a twin-screw extruder for melt extrusion, cooling, and underwater pelletizing to obtain modified particles; the screw speed is 60 rpm; the pelletizer speed is 3000 rpm.
[0073] (4) The modified particles obtained in step (3) are used to prepare foamed beads using a supercritical foaming device under the conditions of a foaming temperature of 100° C., a saturation pressure of 15 MPa, and a saturation pressure time of 30 min, wherein the supercritical foaming gas is CO2 and N2 in a ratio of 3:1; the obtained PHA / PBAT composite foam material has a magnification of 8.4 times.
[0074] (5) The foamed particles obtained in step (4) are placed in a pre-pressurization tank for pressure maintenance, with a compressed air pressure of 1 kg and a pressure maintenance time of 4 hours, and then steam-formed by a steam molding device to obtain a biodegradable thermal insulation foamed thin-wall plastic cup.
[0075] Comparative Example 2
[0076] In this comparative example, the modification and foaming material preparation process of the composite material of Cyanobacteria PHA-BP330 and Jinhui Zhaolong PBAT-1908 is the same as that of Example 1, except that no chain extender is added. The ratio of the obtained PHA / PBAT composite foam material is 9.8 times. The foamed particles are placed in a pre-pressurization tank for pressure maintenance, the compressed air pressure is 1kg, the pressure maintenance time is 4h, and then steam-formed by a steam molding device to obtain a degradable thermal insulation foamed thin-wall plastic cup.
[0077] Comparative Example 3
[0078] In this comparative example, the modification and foaming material preparation process of the composite material of Cyanobacteria PHA-BP330 and Jinhui Zhaolong PBAT-1908 is the same as that of Example 1, except that no self-assembly nucleating agent is added. The magnification of the obtained PHA / PBAT composite foam material is 11.4 times. The foamed particles are placed in a pre-pressurization tank for pressure maintenance, the compressed air pressure is 1kg, the pressure maintenance time is 4h, and then steam-formed by a steam molding device to obtain a degradable thermal insulation foamed thin-wall plastic cup.
[0079] Comparative Example 4
[0080] In this comparative example, the modification and foaming material preparation process of the composite material of blue crystal microorganism PHA-BP330 and Jinhui Zhaolong PBAT-1908 is the same as that in Example 3, except that the weight portion of the self-assembly nucleating agent TMC-328 is 0.5 parts; the ratio of the obtained PHA / PBAT composite foam material is 25.8 times. The foamed particles are placed in a pre-pressurization tank for pressure maintenance, the compressed air pressure is 1kg, the pressure maintenance time is 4h, and then steam-molded by a steam molding device to obtain a degradable thermal insulation foamed thin-wall plastic cup.
[0081] Figure 1 The SEM images of the simple blend of PHA / PBAT in Comparative Example 1 (a) and the improved blend of Example 1 with the addition of a chain extender (b) are shown. Through granulation, it was found that the granulation of the simple blend of PHA and PBAT showed a phase separation phenomenon, with a typical "island structure", such as Figure 1 As shown in (a) in the figure, this phenomenon causes the pores of PHA / PBAT to rupture during the foaming process, and the expansion rate of the foam beads decreases. The epoxy chain extender has the effect of improving the compatibility of the two matrices, and at the same time, a certain branched chain extension structure is generated. Figure 1 It can be seen from (b) that after adding the compatibilizer, the interaction between PHA and PBAT matrix is enhanced, the interfacial compatibility is significantly improved, and the foaming effect is improved.
[0082] Figure 2The SEM images of the bead foaming material in Example 1 with the addition of the self-assembly nucleating agent and in Comparative Example 3 without the addition of the self-assembly nucleating agent are shown in FIG. Figure 2 As shown in (a), a chain extender is introduced into the PHA / PBAT matrix to form a cross-linked grid structure, which improves the melt strength. After adding a self-assembly nucleating agent, a fibril network structure is formed, which induces the PHA / PBAT molecular chain to form heterogeneous nucleation sites, accelerates the crystallization rate, and improves the crystallinity, so that the cell density is significantly increased and the cell size is reduced, so that the wall thickness of the steam-molded plastic cup is thinner, which can be less than 2mm. Figure 2 As can be seen from (b) in the figure, the cell diameter without the addition of nucleating agent is larger, the cell density is low, the particle strength is low, and the foam particles are easy to step on the bubble when the steam is used to form the plastic cup, making it difficult to form.
Claims
1. A supercritical foaming PHA / PBAT composite material, characterized in that: The composition comprises the following components in parts by weight: PHA: 60-90 parts; PBAT: 10-40 parts; Chain extender: 0.5-2.0 parts; Self-assembly nucleating agent: 0.2-0.8 parts; Anti-hydrolysis agent: 0.1-0.5 parts.
2. The supercritical foamed PHA / PBAT composite material according to claim 1, characterized in that: The PHA is at least one of PHB, PHBV, PHBHHx, and P(3HB, 4HB).
3. The supercritical foamed PHA / PBAT composite material according to claim 1, characterized in that: The PBAT has a melt index of ≤7g / 10min and a tensile strength of ≥18Mpa.
4. The supercritical foamed PHA / PBAT composite material according to claim 1, characterized in that: The chain extender is at least one of epoxy chain extenders ADR series, oxazoline and isocyanate.
5. The supercritical foamed PHA / PBAT composite material according to claim 1, characterized in that: The self-assembly nucleating agent is hydrazide and / or amide; the self-assembly nucleating agent is at least one of sebacic acid dibenzohydrazide, adipic acid diphenyl dihydrazide and amide nucleating agent.
6. The supercritical foamed PHA / PBAT composite material according to claim 1, characterized in that: The anti-hydrolysis agent is at least one of carbodiimide, isocyanate and acid anhydride.
7. A method for preparing the supercritical foaming PHA / PBAT composite material according to claim 1, characterized in that: The following steps are involved: (1) mixing PHA and PBAT, adding a chain extender, a self-assembly nucleating agent and an anti-hydrolysis agent, and stirring to obtain mixed particles; (2) melt-mixing and extruding the mixed particles through a twin-screw extruder, pelletizing the particles underwater to obtain modified particles, and drying the particles; (3) The dried modified particles are subjected to supercritical foaming to obtain supercritical foamed beads.
8. The method for preparing the supercritical foaming PHA / PBAT composite material according to claim 7, characterized in that: In step (3), the supercritical foaming gas is one or both of supercritical CO2 and supercritical N2; the foaming temperature is 100-120°C, the saturation pressure is 10-20MPa, and the pressure holding time is 10-30min.
9. Use of the supercritical foamed PHA / PBAT composite material according to claim 1 in preparing a degradable thermal insulating thin-walled plastic cup.
10. The use of the supercritical foamed PHA / PBAT composite material according to claim 9 in the preparation of thermal insulation thin-wall plastic cups, characterized in that: The supercritical foamed PHA / PBAT composite material is pre-pressed and then steam-formed to obtain a biodegradable thermal insulation foamed plastic cup.
Citation Information
Patent Citations
Biodegradable poly (butylene adipate terephthalate) micro-pore foaming particle with high foamability and preparation method thereof
CN102229707A
Foaming composition, biodegradable foam and preparation method thereof
CN118215711A
Cited By
PBAT (poly (butylene adipate-co-terephthalate))-based degradable composite foam material as well as single-kettle one-step preparation method and application thereof
CN121949867A
Pbat-based degradable composite foamed material and one-pot one-step preparation method and application thereof
CN121949867B